Recent status of Banteng (Bos Javanicus) conservation in East Java and its perspectives on ecotourism planning - Hakim, Luchman; Guntoro, Dodit Ari; Waluyo, Joko; Sulastini, Dian; Hartanto, Lugi; Nakagoshi, Nokukazu (Journal of Tropical Life Science, 2015)
The aims of this article are to examine the recent status ofÂ Banteng Bos javanicus conservation in East Java, identify the roots of conservation problems and propose the non-consumptive and sustainable uses of Banteng by implementing ecotourism. Recently, Banteng population distributes in Alas Purwo, Meru Betiri, and Baluran National Parks. Â The population in Alas Purwo and Meru Betiri were relatively stable yearly. Rapid population decrease found in Baluran National Park. The roots of threats may be categorized into two factors, socio-economic and ecological factors. Socio-economic problems lead to the increase of habitat disturbance, poaching, and illegal hunting. Ecological aspect was ranging from invasion of exotic plant species, competitors, predators, drought, forest fire and vegetation changes. Lack of habitat management also recognized as an important factor to drive Bos javanicus decline and extinction. Ecotourism in the national park may become one of the significant and effective stimuli to support Banteng conservation.